Introducing culture and critical thinking in the classroom: Analysing multimodal texts from NGOs in a Masters course - Martínez Lirola, María; Ibáñez Castejón, Laura (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2022)
The multimodal nature of present societies makes clear that teaching with authentic multimodal texts can contribute to bringing different cultural realities into the classroom. For this reason, it was decided to use texts published by Non Governmental Organizations (NGOs) in order to teach visual grammar (Kress and van Leeuwen, 2006) in a Masters course in Spain. These texts were also selected because they are appropriate to teach cultural aspects, and raise awareness of the realities of poor countries; they may also foster the acquisition of interpersonal competencies. This paper offers textual analysis; this research will point out that teaching students to be critical with the discourse produced by NGOs is essential in order to unveil relationships of domination and power because discourse is always a powerful tool used to reproduce social reality.